Relationship Between Udder Morphometry and Somatic Cell Count in Barbari Goats - Varsha Gupta (Indian Journal of Veterinary Anatomy, 2022)
The present study was aimed to characterize the external morphological traits of udder of Barbari goats and its relationship with somatic cells in the milk for identification of probability of subclinical mastitis. For present study 40 Barbari goats were reared in Goat farm, DUVASU, Mathura. Udder of Barbari goats was either bowl or cylindrical shaped and teats were of funnel, cylindrical and bottle shaped. Number of goats with bowl shaped udder were predominant than the cylindrical shaped udder. Various dimensions of udder viz. length, diameter, depth and cleft were higher in bowl shaped udder. Somatic cell count was ranged between 25,267.00 to 80,263.00 and 53,850.00 to 2, 26,280.00 in bowl and cylindrical shaped udder, respectively. It seems that the goats with cylindrical shaped udder were more prone for subclinical mastitis due to higher number of somatic cell count.